ELEMENTAL ANALYSIS OF PIGMENTS IN THE CERAMIC HUACO “THROAT-CUTTER WARRIOR WITH TROPHY” USING X-RAY FLUORESCENCE SPECTROSCOPY - Luizar Obregon, C.; Zamalloa Jara, M. A.; Contreras, K. (Journal of the Chilean Chemical Society, 2019)
The X-ray fluorescence spectroscopy technique was used, with a portable equipment, to analyze traces of elements, in a ceramic piece, commonly called “huaco”, identified as the “Throat-Cutter Warrior with Trophy”, and related to the Moche Culture (between 100 and 800 years a.D.) that developed on Peru´s north coast. The analysis has been made in the coatings of red, brown, orange and white color, in the matrix-paste and in the NIST2711a standard. In the ceramic piece, the presence of Iron was confirmed, in greater quantity, in the overlapped layers of red and brown color, while, in the white pigment, elements of Zinc and Barium were detected, considering that the latter never had been reported in Moche ceramic. In the areas corresponding to the eyes, of metallic aspect, 91% copper has been detected. It is argued that the similitude in iconography and materials would indicate that we are dealing with an ancient piece.